PENERAPAN POLA HIDUP SEHAT DALAM UPAYA PENCEGAHAN STUNTING , ANAK SEHAT KELUARGA KUAT DAN BAHAGIA DI DESA PANANGGAHAN KECAMATAN SORKAM KAB. TAPANULI TENGAH - Tanjung, Mansur; Riwayani, Riwayani; Hj. Nelly Azwarni Sinaga, Hj. Nelly; Lukman Hakim Hutagalung, Lukman Hakim; Khairil Safli Pohan, Khairil Safli (Cattleya Darmaya Fortuna, 2025)
Implementing a healthy lifestyle plays a crucial role in preventing stunting, particularly among children and pregnant women. Additionally, economic factors, such as low per capita family income (below the poverty line), can also contribute to the occurrence of stunting. The objective of the Community Partnership Service (PKM) program in Pananggahan Village, Sorkam District, Central Tapanuli Regency, with the theme 'Implementing a Healthy Lifestyle to Prevent Stunting: Healthy Children, Strong and Happy Families,' is to: (1) Support Optimal Growth: A healthy lifestyle, including balanced nutrition, plays a key role in ensuring that children receive the essential vitamins and minerals needed to support optimal physical growth and brain development. (2) Strengthen the Immune System: Healthy food, physical activity, and good hygiene practices help strengthen children's immune systems, making them less prone to infections. Recurrent infections can exacerbate the risk of stunting, as the body struggles to absorb nutrients effectively. (3) Prevent Nutrient Deficiencies: A healthy lifestyle encourages the consumption of nutritious foods in adequate amounts, preventing deficiencies in essential micronutrients such as iron, calcium, vitamin A, and zinc. Long-term nutrient deficiencies are a primary cause of stunting. With a proper healthy lifestyle, the risk of stunting can be reduced, as children receive the support necessary for growth and development in line with their full potential.